Behavior of MHD Waves in Plasma in Gravitational Field - Jovanovic, Gordana (Current Approaches in Science and Technology Research Vol. 13, 2021)
Using magnetohydrodynamic equations (MHD), we investigate plasma waves. This magnetohydrodynamic model for isothermal, gravitationally stratified plasma in a horizontal inhomogeneous magnetic field yields the dispersion equation and reflection coefficient for MHD waves. The speeds of Alfven and sound are both constant. For linearized per turbations, analytical solutions can be derived using this approach. They show the Alfven mode, as well as the fast and slow magnetoacoustic modes. Gravity has an effect on these modes. The dispersion equation describes gravito-acoustic waves in the nonmagnetized situation.